Multiplicity of Positive Solutions for a Second-Order Elliptic System of Kirchhoff Type - S. Khademloo; E. Valipour; A. Babakhani (Abstract and Applied Analysis)
We study elliptic problems of Kirchhoff type in Ω⊂RN  (N≥3). Using variational tools, we establish the existence of at least two nontrivial and nonnegative solutions.